Liquid Crystalline Networks toward Regenerative Medicine and Tissue Repair. Issue 46 (17th October 2017) - Martella, Daniele; Paoli, Paolo; Pioner, Josè M.; Sacconi, Leonardo; Coppini, Raffaele; Santini, Lorenzo; Lulli, Matteo; Cerbai, Elisabetta; Wiersma, Diederik S.; Poggesi, Corrado; Ferrantini, Cecilia; Parmeggiani, Camilla
Abstract: The communication reports the use of liquid crystalline networks (LCNs) for engineering tissue cultures with human cells. Their ability as cell scaffolds for different cell lines is demonstrated. Preliminary assessments of the material biocompatibility are performed on human dermal fibroblasts and murine muscle cells (C2C12), demonstrating that coatings or other treatments are not needed to use the acrylate‐based materials as support. Moreover, it is found that adherent C2C12 cells undergo differentiation, forming multinucleated myotubes, which show the typical elongated shape, and contain bundles of stress fibers. Once biocompatibility is demonstrated, the same LCN films are used as a substrate for culturing human induced pluripotent stem cell‐derived cardiomyocites (hiPSC‐CMs) proving that LCNs are capable to develop adult‐like dimensions and a more mature cell function in a short period of culture in respect to standard supports. The demonstrated biocompatibility together with the extraordinary features of LCNs opens to preparation of complex cell scaffolds, both patterned and stimulated, for dynamic cell culturing. The ability of these materials to improve cell maturation and differentiation will be developed toward engineered heart and skeletal muscular tissues exploring regenerative medicine toward bioartificial muscles for injured sites replacement. Abstract : Liquid crystalline networks are demonstrated as powerful scaffolds for different cell lines. Demonstration of complete adhesion on bare films by seeding murine muscle cells and human dermal fibroblasts is shown. By seeding single human induced pluripotent stem cell‐derived cardiomyocytes, the promotion of a more mature cell phenotype in a short period of culture while maintaining the integrity of film potential is demonstrated.